Pelatihan Pola Asuh Gizi dengan Website (Simpatik) Melalui Bina Keluarga Balita di Wilayah Kerja Puskesmas Paal Merah 2 Kota Jambi - Ary Irfan; Egy Sunanda Putra; Junita Junita (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Feeding practices low contribution for toddlers are closely related to the knowledge, motivation and attitudes of mothers/caregivers of toddlers. In Indonesia, the knowledge of mothers or caregivers is one of the factors that makes it difficult to handle malnutrition problems. The aim of community service is to increase the knowledge of mothers of toddlers in providing MP-ASI. Community service activities in collaboration with the Paal Merah II Community Health Center, Jambi City with a target of 40 mothers of toddlers at Posyandu Anggrek 9 conducting training on the application of science and technology research results in the form of the SIMPATIK website. Implementation of community service activities is carried out in three stages, namely: training in nutritional parenting patterns through SIMPATIK, and evaluation of knowledge of nutritional parenting patterns (pretest-posttest). As a result of the activity, 95% of mothers had good knowledge in giving MP-ASI, which previously was 15%, meaning there was an increase of 80%. SYMPATHIC training increases the knowledge of mothers of toddlers which can later contribute to the behavior of giving MP-ASI, so that providing the right MP-ASI will provide benefits and suit optimal growth and development according to age. Partners contribute to providing posyandu premises, accompanying teams of nutrition implementers and posyandu cadres. Obstacles during service are mothers of toddlers' limited time to attend training, and some mothers do not have data packages. These obstacles and challenges can be overcome by providing a mentoring team, and providing data packages to mothers of toddlers so they can access SIMPATIK